2003
DOI: 10.1002/mrd.10307
|View full text |Cite
|
Sign up to set email alerts
|

9‐cis‐retinoic acid during in vitro maturation improves development of the bovine oocyte and increases midkine but not IGF‐I expression in cumulus‐granulosa cells

Abstract: The isomer 9-cis of retinoic acid (9-cis-RA) exerts a beneficial effect on bovine in vitro development when added to in vitro maturation (IVM) culture. In the present work, 9-cis-RA 5 nM was found to be stimulatory as opposed to 500 nM (toxic). Cumulus-oocyte complexes (COCs) were treated with the found physiological dose 9-cis-RA 5 nM, and the next determinations performed: (1) relative expression of midkine (MK) and IGF-I, by reverse transcriptasepolymerase chain reaction (RT-PCR), in cumulusgranulosa cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
46
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 36 publications
(52 citation statements)
references
References 72 publications
6
46
0
Order By: Relevance
“…In agreement with these findings, the addition of 9-cis-RA to in vitro maturation (IVM) cultures stimulated cortical granule migration in bovine oocytes both matured and meiotically arrested for a 24-hr culture period (Duque et al, 2002). Increased embryonic development (Duque et al, 2002;Gómez et al, 2003;Hidalgo et al, 2003), embryonic quality (Duque et al, 2002;Hidalgo et al, 2003), cryopreservation tolerance (Duque et al, 2002;Gómez et al, 2003), and pregnancy rates , were also obtained after oocyte maturation with 9-cis-RA. Recently, we showed increased midkine expression in bovine cumulus-granulosa cells in response to RA .…”
Section: Introductionsupporting
confidence: 65%
See 2 more Smart Citations
“…In agreement with these findings, the addition of 9-cis-RA to in vitro maturation (IVM) cultures stimulated cortical granule migration in bovine oocytes both matured and meiotically arrested for a 24-hr culture period (Duque et al, 2002). Increased embryonic development (Duque et al, 2002;Gómez et al, 2003;Hidalgo et al, 2003), embryonic quality (Duque et al, 2002;Hidalgo et al, 2003), cryopreservation tolerance (Duque et al, 2002;Gómez et al, 2003), and pregnancy rates , were also obtained after oocyte maturation with 9-cis-RA. Recently, we showed increased midkine expression in bovine cumulus-granulosa cells in response to RA .…”
Section: Introductionsupporting
confidence: 65%
“…The gene sequences activated or repressed by RA at meiotic arrest, leading to increased polyadenylation, could therefore explain part of the effects on development observed in former oocyte studies (Duque et al, 2002;Gómez et al, 2003;Hidalgo et al, 2003). These changes included increased expression in granulosa cells of midkine , a retinoid responsive gene, whose recombinant peptide product stimulates embryonic development in vitro up to the blastocyst stage (Ikeda et al, 2000a,b).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this manner, Mohan et al have shown that cumulus granulosa cells contain endogenously activated retinoid receptors that can reply to RA [19]. The beneficial effects of RA on in vitro maturation of cumulus oocyte complexes has been previously described [5,6,12,20,21] however no reports have discussed the effects of RA on the developmental competence of naked immature oocytes. In a previous study, we have shown that the use of a physiological dose of all-trans retinoic acid (t-RA; 2 μM) during in vitro maturation and under precise conditions could improve both maturation and developmental competence of denuded immature mouse oocytes [22].…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study, we have shown that the use of a physiological dose of all-trans retinoic acid (t-RA; 2 μM) during in vitro maturation and under precise conditions could improve both maturation and developmental competence of denuded immature mouse oocytes [22]. Therefore, based on this and other studies [5,6,12,[19][20][21][22] we assume that the cumulus granulosa cells might be a target for added RA during in vitro maturation, which could improve embryo development. In this study, we evaluate the effects of t-RA in association with a co-culture granulosa cell monolayer on the IVM of naked immature mice oocytes and then follow them until the blastocyst stage.…”
Section: Introductionmentioning
confidence: 99%